Pemanfaatan Elektrik Bioretensi dalam Menurunkan Kadar Escherichia coli dan Total Bakteri Koliform Sebagai Upaya Peningkatan Kualitas Air pada Drainase Perkotaan - Endah Lestari (KILAT, 2021)
Rapid development in a watershed affects surface and ground water sources. Urbanization results in increased environmental pollution and groundwater pollution. Best water resource management practices are Low Impact Development (LID) such as bioretention, vegetative swales, permeable pavements, and rainwater wetlands have been implemented to reduce the adverse effects of urbanization such as flooding by reducing peak runoff on the surface and thereby managing rainwater runoff. The purpose of this study was to analyze microbial contamination in wastewater originating from city drainage channels. The research was carried out experimentally by taking water in Item River, Kemayoran directly and put it in an electric bioretention tank. The rain-wastewater-bioretention (RWB) tank is in the form of a watertight tank measuring 60 cm in diameter by 80 cm in height with a medium of 50 cm, leaving 30 cm to provide space and time for standing water during infiltration time. The results of the water taken on the 2nd day through Bioretention carried out laboratory testing with the scope of Microbiological analysis of Environmental Health Quality Standards, Escherichia coli levels decreased from 17 APM/100 ml to 9 APM/100 ml. In addition, total Coliform levels from 2800 APM/100 ml to 270 APM/100 ml.